SafeSpace: what is the feasibility and acceptability of a codesigned virtual reality intervention, incorporating compassionate mind training, to support people undergoing cancer treatment in a clinical setting?. Issue 2 (10th February 2022) - O'Gara, Geraldine; Murray, Lisa; Georgopoulou, Sofia; Anstiss, Tim; Macquarrie, Andrew; Wheatstone, Pete; Bellman, Barbie; Gilbert, Paul; Steed, Anthony; Wiseman, Theresa
Abstract : Objectives: The SafeSpace study codesigned and tested a virtual reality (VR) intervention, incorporating relaxation and compassionate mind training to determine acceptability/feasibility in an oncology setting and evaluate impact on physical/psychological well-being and quality of life. Design: A two-phase study. Phase I determined key characteristics using an experienced-based codesign approach. Phase II evaluated the intervention using various measures and qualitative interviews in a mixed methods approach. Descriptive statistics were used to analyse measures data and framework analysis to analyse interviews. Setting: A specialist cancer centre, UK. Participants: 11 in phase I and 21 in phase II. Participants were in cancer treatment, recovery or palliative care. Primary and secondary outcome: Primary outcome: acceptability of the intervention, assessed by >60% uptake of three sessions. Secondary outcomes: impact on psychological well-being using EQ-5D/QLQ-C30, Profile of Mood Scale, Warwick and Edinburgh Mental Well-being Scale, Depression and Anxiety Severity Scale 21, Self-Compassion Scale, Acceptance and Action Questionnaire and a locally developed questionnaire to capture self-compassion post use. Physiological impact was assessed by change in heart rate (HR)/HR variability and electrodermal activity (EDA). Results: Twenty participants (mean age=48.7 years; SD=16.87); 65% (n=13) completed three sessions. Mental well-being improved following each use and from baseline to after session 3 (VR 1—z=2.846, p≤0.01; VR 2—z=2.501, p≤0.01; VR 3—z=2.492, p≤0.01). There was statistically significant difference in mean scores for EDA at mid-session and post session compared with pre session ( F (1.658, 4.973)=13.364, p<0.05). There was statistically significant reduction in stress levels from baseline to post session 3. Participants found the intervention acceptable and highlighted areas for development. Conclusion: The intervention is acceptable and feasible and has shown positive effects on mental well-being/stress in the oncology setting. Larger studies are needed to confirm findings.